Program razvoja za održivi ruralni turizam u Moslavini (University of Maribor Press, 2020)
The Development Program for the Sustainable Rural Tourism in Moslavina. Present book is the result of a project, with which we wanted to stimulate sustainable rural tourism across the Croatian region of Moslavina. Moslavina is positioned in Central Croatia, which has a very favourable position between Slovenia, Bosnia and Herzegovina and Serbia. With its natural resources, it has great potential for sustainable tourism development. Many family farms (OPGs), which have a tourist offer, are a great attraction for tourists as also the nature of Lonjsko Polje Park and Moslavina Mountain. Tutors and 1st year students of the Master’s program Tourism at the Faculty of Tourism University of Maribor addressed the strategic challenge of the tourism development together by participatory planning and involvement of local community. After the analysis of the situation, they prepared a development vision, identified the priority areas of work, defined the indicators and the way they would be monitored. The action plan itself is based on the theory of sustainable tourism development in protected areas, presented at the beginning of this book. Monografija Program razvoja za održivi ruralni turizam u Moslavini rezultat je projekta kojim želimo potaknuti održivi ruralni turizam na širem teritoriju hrvatske regije Moslavine. Moslavina je pozicionirana u središnjoj Hrvatskoj i ima vrlo pogodan položaj između Slovenije, Bosne i Hercegovine i Srbije. Sa svojim prirodnim bogatstvima ima veliki potencijal razvoja turizma i, još više, održivog turizma. Mnoštvo obiteljskih poljoprivrednih gospodarstava (OPG-ovi) koja imaju turističku ponudu odlična su atrakcija za održivi turizam, kao i priroda parka Lonjsko polje i Moslavačka gora. Mentori i studenti prve godine postdiplomskog programa Turizam na Fakultetu za turizam Sveučilišta u Mariboru (Slovenija) uz sudjelovanje lokalnog stanovništva suočili su se sa strateškim izazovom razvoja turizma. Nakon analize stanja, pripremili su viziju razvoja, utvrdili prioritetna područja rada, definirali mjere i pokazatelje te način praćenja istih. Sam akcijski plan temelji se na teoriji razvoja održivog turizma u zaštićenim područjima, predstavljenoj na početku ove monografije.